Profiling of oxBS-450K 5-hydroxymethylcytosine in human placenta and brain reveals enrichment at imprinted loci. Issue 2 (1st February 2018) - Hernandez Mora, Jose Ramon; Sanchez-Delgado, Marta; Petazzi, Paolo; Moran, Sebastian; Esteller, Manel; Iglesias-Platas, Isabel; Monk, David
ABSTRACT: DNA methylation (5-methylcytosine, 5 mC) is involved in many cellular processes and is an epigenetic mechanism primarily associated with transcriptional repression. The recent discovery that 5 mC can be oxidized to 5-hydromethylcytosine (5hmC) by TET proteins has revealed the "sixth base" of DNA and provides additional complexity to what was originally thought to be a stable repressive mark. However, our knowledge of the genome-wide distribution of 5hmC in different tissues is currently limited. Here, we sought to define loci enriched for 5hmC in the placenta genome by combining oxidative bisulphite (oxBS) treatment with high-density Illumina Infinium HumanMethylation450 methylation arrays and to compare our results with those obtained in brain. Despite identifying over 17, 000 high-confidence CpG sites with consistent 5hmC enrichment, the distribution of this modification in placenta is relatively sparse when compared to cerebellum and frontal cortex. Supported by validation using allelic T4 β-glucosyltransferase assays we identify 5hmC at numerous imprinted loci, often overlapping regions associated with parent-of-origin allelic 5 mC in both placenta and brain samples. Furthermore, we observe tissue-specific monoallelic enrichment of 5hmC overlapping large clusters of imprinted snoRNAs-miRNAs processed from long noncoding RNAs (lncRNAs) within the DLK1-DIO3 cluster on chromosome 14 and SNRPN-UBE3A domain on chromosome 15. Enrichment is observed solely on the transcribed alleles suggesting 5hmC is positively associated with transcription at these loci. Our study provides an extensive description of the 5hmC/5 mC landscape in placenta with our data available at www.humanimprints.net, which represents the most comprehensive resource for exploring the epigenetic profiles associated with human imprinted genes.